Continuous strain tuning of oxygen evolution catalysts with anisotropic thermal expansion - Yu Du; Fakang Xie; Mengfei Lu; Rongxian Lv; Wangxi Liu; Yuandong Yan; Shicheng Yan; Zhigang Zou (Nature Communications, 2024)
Abstract Compressive strain, downshifting the d-band center of transition metal oxides, is an effective way to accelerate the sluggish kinetics of oxygen evolution reaction (OER) for water electrolysis. Here, we find that anisotropic thermal expansion can produce compressive strains of the IrO6 octahedron in Sr2IrO4 catalyst, thus downshifting its d-band center. Different from the previous strategies to create constant strains in the crystals, the thermal-triggered compressive strains can be real-timely tuned by varying temperature. As a result of the thermal strain accelerating OER kinetics, the Sr2IrO4 exhibits the nonlinear lnj o - T −1 (j o, exchange current density; T, absolute temperature) Arrhenius relationship, resulting from the thermally induced low-barrier electron transfer in the presence of thermal compressive strains. Our results verify that the thermal field can be utilized to manipulate the electronic states of Sr2IrO4 via thermal compressive strains downshifting the d-band center, significantly accelerating the OER kinetics, beyond the traditional thermal diffusion effects.